Myt brewer - part b - Mendonca, Valerie, (SAGE Business cases., 2024)
Kasliwal decided to deploy one of the latest prototypes and continue improving on a subsequent version. He leased out a couple of machines to offices and cafes and observed how customers interacted with the machine. Based on customers’ experience and feedback, he set out to create new and improved prototypes. The next dilemma he faced was increasing revenue by charting a growth course for his product.